ANALISIS PENGARUH KUALITAS PRODUK, HARGA, DESAIN PRODUK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK SARUNG TINJU MEREK â€œAN-DAâ€ DI JAWA TENGAH - Firdaus, Faisal; Sudaryanto, Budi (Diponegoro Journal of Management, 2017)
Sports is very important today and has become a worldwide trend, with this phenomenon there is also an increasing trend in sports product. This study aims to analyze the influence of product quality, price, product design, and word of mouth of AN-DA boxing gloves purchase decision in Central Java. Product quality, price, product design, and word of mouth are matters that are considered before buying a pair of boxing gloves and are providing value to customers in choosing boxing gloves that have become the needs for athletes in Central Java. Sampling method used in this study is purposive sampling. Data were collected from 100 respondents who have met the criteria of ever purchasing and using AN-DA boxing gloves and are domiciled in Central Java. The analytical methods used in this study include validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient determination test, F test and t test using IBM SPSS Statistics version 24. The results show that the variables of product quality, price, product design, and word of mouth have positive and significant impact on purchase decision by the regression equation. Product quality is the most influential variable on purchasing decisions followed by product design, price and word of mouth. Four independent variables are contributing 66.2% to the purchase decision. While the remaining 33.8% is influenced by other variables outside of this study.